Impact of institutional quality on firms' debt maturity in developing nations - Matemilola, Bolaji Tunde; Bany-Ariffin, A.N.; Gbemisola, Adeoye (Inderscience Publishers, 2023)
This article investigates the impacts of institutional quality on debt maturity using 3,885 listed firms from 22 developing nations. This study specifies the dynamic panel models and applies the two-step system generalised method of moments' estimation that reduces the reverse-causality problem. The findings reveal that the average institutional quality index has positive impacts on debt maturity in developing nations. Furthermore, regulatory quality, rule of law, and control of corruption have positive impacts on debt maturity, separately. Moreover, institutional quality has positive impacts on debt maturity of listed firms in developing nations where legal enforcement quality is high, but it has negative impacts on the debt maturity of firms in developing nations where legal enforcement quality is low. The overall findings suggest that strong institutional quality and legal enforcement reduce bankruptcy costs; these encourage lenders to provide firms debt capital with long-term maturity.